Vaccination against SARS-CoV-2 and its relationship with public interest in mental health: a study between 2020-2022 in Spain - Becerra-García, Juan Antonio; Barbeito, Sara; Calvo, Ana; Sánchez-Gutiérrez, Teresa (Psychology, Health and Medicine, 2023)
The possible relationship between vaccination against SARS-CoV-2 (COVID-19) and mental health has been largely unexplored. We investigated variations in public interest in mental health issues between the different periods of the vaccination campaign against SARS-CoV-2 in Spain and before the initiation of the campaign. Using Google Trends, we explored the relative search volume (RSV) for the terms ‘anxiety’, ‘depression’, ‘stress’, ‘insomnia’, and ‘suicide’ between 03/01/2020 and 01/15/2022. The RSV was compared for these terms with respect to four periods: the pre-vaccination pandemic period; the period running from initiation of vaccination until 50% of the population was fully vaccinated (FV); the period running from 50% FV to 70% FV; and the period after 70% FV. Differences in the RSV indices were observed between the studied periods for ‘anxiety’(F = 6.07; p = 0.001; ƞ2 = 0.16), ‘stress’ (F = 7.77; p < 0.001; ƞ2 = 0.19), and ‘insomnia’ (F = 3.80; p = 0.013; ƞ2 = 0.11). A lower RSV was found for ‘anxiety’, ‘stress’, and ‘insomnia’ after 70% FV compared to the two previous vaccination periods. A lower RSV was also found for ‘stress’ after achieving the milestone of 70% FV in relation to the period prior to initiation of the campaign. In conclusion, there is less need for information on specific mental health topics in the period after 70% FV. In Spain, reaching this vaccination milestone may have had a positive impact on anxiety, stress, and insomnia levels in the population, as reflected in fewer web searches for information on these psychopathological processes. The promotion of the COVID-19 vaccination campaign could take into account the changes observed in this preliminary study with respect to public interest in stress, anxiety, and insomnia once a large percentage of the population has been vaccinated.
Keywords: COVID-19; internet use; mental health; public health; Sars-CoV-2; vaccine; Scopus; JCR